Controlled released naringin-loaded liposome/sucrose acetate isobutyrate hybrid depot for osteogenesis in vitro and in vivo - Meng, Di; Song, Jinlin; Yi, Yin; Li, Jihong; Zhang, Ting; Shu, Yu; Wu, Xiaohong (Frontiers in Bioengineering and Biotechnology, 2023)
A common problem in bone tissue engineering is that the burst release of active osteogenic factors is not beneficial for osteogenesis. This study aimed to prepare naringin (Ng) liposomes to reduce the burst release of Ng and improve osteogenesis. Herein, we synthesized Ng liposomes using the thin-film hydration method. Drug-encapsulation efficacy experiments were conducted using the ultracentrifugation technique. The morphology and size distributions of freeze dried liposomes were determined by transmission electron microscopy and dynamic light scattering. The Ng liposomes and Ng-lipo/sucrose acetate isobutyrate (SAIB) depots were characterized using Fourier transform infrared spectroscopy and in vitro release studies. After implantation of the Ng lipo/SAIB depots, in vitro osteoblast-liposome interactions and in vivo osteogenesis were tested. The formulation of freeze-dried Ng liposomes via an optimized recipe yielded nanosized (136.9 nm) negatively charged particles with a high encapsulation efficiency (~76.3%). Their chemical structure did not change after adding SAIB to the Ng liposomes. The burst release was reduced dramatically from 74.4% to 23.7%. In vivo, after 8 weeks, the new bone formation rate in the calvarial defects of Sprague-Dawley rats receiving Ng-lipo/SAIB was 57% compared with 25.18% in the control group (p = 0.0003). Our results suggested that Ng-lipo/SAIB hybrid depots could serve as candidate materials for drug delivery in bone regeneration applications.